Estimating the impact of school feeding programs: Evidence from mid day meal scheme of India. (October 2021) - Kaur, Randeep
Highlights: This paper uses instrumental variable approach to study the world's largest free school meal program (i.e., Mid Day Meal Scheme or "MDMS") on primary school enrollment in India. This paper finds that the MDMS program had positive and significant impact on gross and net primary school enrollment in India.  MDMS increased gross and net enrollment in primary school by 16 to 19 percentage points.  An analysis of on-time enrollment finds that the program had a large effect on net enrollment in the first grade, suggesting a large extensive margin response. MDMS had a larger impact on (a) girls compared to boys and (b) disadvantaged population groups compared to other population groups in India. The analysis found the effect of the mid-day meal program on girls to be almost twice its effect on boys for primary school enrollment, suggesting that the program had a positive impact on reducing the gender gap in school participation. Findings of this paper suggests that school feeding program is an effective policy tool for increasing primary school enrollment in developing countries. Abstract: This paper studies the impact of the world's largest free school lunch program (Mid Day Meal Scheme) on school enrollment in India. While the program was launched nationally, its implementation has been scattered within and across states. Using an instrumental variable approach, this paper estimates local average treatment effect of receiving free meals in school on children's enrollment in primary school. The findings of this paper suggest that the mid-day meal scheme increased the probability of enrollment in primary school and on-time enrollment in first grade. An analysis of heterogeneity in results shows that the program had larger effect on socially disadvantaged groups and on girls. Specifically, the analysis found the effect of the mid-day meal program on girls to be almost twice its effect on boys for primary school enrollment, suggesting that the program had a positive impact on reducing the gender gap in school participation.